2013
DOI: 10.1111/appy.12103
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of Patient Health Questionnaire-9 and Patient Health Questionnaire-2 to screen for depression among college students in China

Abstract: The PHQ-9 and the PHQ-2 are valid and reliable tools to screen depression in Chinese college students. For screening purposes, cutoff scores of 11 and 3 are recommended for PHQ-9 and PHQ-2, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
257
1
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 309 publications
(273 citation statements)
references
References 35 publications
8
257
1
7
Order By: Relevance
“…Meanwhile, several studies have shown that the Chinese version of PHQ‐9 is a valid and reliable tool for screening depression (Chen, Wang, et al, ; Liu et al, ; Wang et al, ; Yu, Tam, Wong, Lam, & Stewart, ). Evidence of feasibility of the PHQ‐9 is also reported among Chinese university students (Zhang et al, ).…”
Section: Introductionsupporting
confidence: 82%
“…Meanwhile, several studies have shown that the Chinese version of PHQ‐9 is a valid and reliable tool for screening depression (Chen, Wang, et al, ; Liu et al, ; Wang et al, ; Yu, Tam, Wong, Lam, & Stewart, ). Evidence of feasibility of the PHQ‐9 is also reported among Chinese university students (Zhang et al, ).…”
Section: Introductionsupporting
confidence: 82%
“…The PHQ-2 is widely used in large populations for depression screening given its brevity, high reliability as well as its established correlation with HRQoL outcomes. 44,45,69,70 Consistent with literature, the PHQ-2 was inversely correlated with both PCS-12 as well as MCS-12 of the SF-12v2 after controlling for the previously mentioned covariates (Tables 3 and 4). 45 Further, we have accounted for the number of prescription medications that patients take for depression, which could be used as a proxy of depression severity, and found it to have a negative and significant association with the MCS-12 of the SF-12v2 (Table 4).…”
Section: Discussionsupporting
confidence: 85%
“…Participants completed the Patient Health Questionnaire (PHQ-9), a depression screen that has been validated in college students. [29][30][31] This screen assesses the frequency over the past 2 weeks of each of nine symptoms based on the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (DSM-IV) criteria for major depression, such as depressed mood and anhedonia; responses are on a Likert scale ranging from 0 (''not at all'') to 3 (''nearly every day''). 32,33 PHQ-9 scores range from 0 to 27, with depression categorization cutoffs of 5 (mild), 10 (moderate), 15 (moderately severe), and 20 (severe).…”
Section: Methodsmentioning
confidence: 99%